E0300 Relationship of polymorphism of apolipoprotein E alleles with coronary heart disease. (17th November 2010) - Yangchun, Zou; Dayi, Hu; Qiguang, Tong; Liujian, Xu; Xingyuan, Jia
Abstract : Objective: To study the relationship of the apolipoprotein (apo) E with coronary heart disease (CHD). Methods: We studied 68 patients with CHD and 59 control subjects without CHD. Polymorphism of ApoE alleles were measured by PCR, Hhal enzyme digestion and polyacrylamide gel electrophoresis. Results: TC, TG, LDL-c, apoB, LP (a) level of CHD group were higher than control (p<0.05); There were significant differences in gene frequency of apo E alleles between CHD and control group but HDL, ApoA1 level of CHD group were lower than control; when compared between the E3 and the E4, the E2 frequency were related with CHD (RR=3.5611, 95% CI 1.1693 to 6.8963, p<0.01). Conclusion: ApoE gene polymorphisms affects serum TC, LDL-C, apoB and LP (a) levels in CHD and apoE allele E2 is a risk factor in the occurrence of CHD.